Implementation of The Student Teams Achievement Division (STAD) Cooperative Model to Practice Student Collaboration and Communication Skills on Electrolyte and Non-Electrolyte Solutions Materials - Lathifatul Hikmah; Rudiana Agustini (Universitas Lampung, 2022)
The right learning model can train students' collaboration skills and communication skills during the learning process. This study aims to describe the implementation of learning through the application of the STAD type cooperative learning model on electrolyte and non-electrolyte solutions and to describe students' collaboration and communication skills during learning. This study uses a pre-experimental method with a research design that is a one-shot case study. The target of this research is the students of class X IPA 2 at SMAN 14 Surabaya with 36 students. The results of this study are 1) The implementation of the syntax of the STAD cooperative learning model at the first meeting got an average percentage score of 96.5% and at the second meeting it was 93.6%, both of which were in the very good category . 2) Students' collaboration skills at the first meeting had an average percentage score of 89.5% and at the second meeting it was 94.5%, both of which were in the very good category. 3) Students' communication skills include the quantity and quality of questioning and opinionating skills. The percentage of quantity scores asking and giving opinions at meetings 1 and 2, respectively, is 47% and 87%. The quality of asking students who obtained good criteria at meeting 1 was 13.89% and at meeting 2 was 16.67%, the percentage of quality opinion of students who obtained good criteria during 2 meetings was 22.22% and 41.67%. Based on the results of the study, it can be concluded that a cooperative learning model like STAD can train students' cooperation and communication skills, which is indicated by an increase in cooperation skills. and student communication during 2 academic meetings and were included in the good category.DOI: http://dx.doi.org/10.23960/jppk.v11.i1.2022.07